2013
DOI: 10.1073/pnas.1214326110
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent reciprocal RNA chimera involving YPEL5 and PPP1CB in chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is the most common form of leukemia in adults in the Western hemisphere. Tumor-specific chromosomal translocations, characteristic findings in several human malignancies that directly lead to malignant transformation, have not been identified in CLL. Using paired-end transcriptome sequencing, we identified recurrent and reciprocal RNA chimeras involving yippee like 5 (YPEL5) and serine/threonine-protein phosphatase PP1-beta-catalytic subunit (PPP1CB) in CLL. Two of seven inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 48 publications
1
36
1
Order By: Relevance
“…We also analyzed other cancer studies where chimeric genes have been reported. In our full set of chimeric junctions (see Methods section ''Chimeric junctions'') we found five chimeric read-through events previously identified, LAMTOR1-ANAPC15 and PTPRG-C3orf14 in melanoma (Berger et al 2010), TATDN1-MTSS1 and MAP2K7-SNAPC2 in CLL (Velusamy et al 2013), and TTTY15-USP9Y found in prostate cancer and experimentally validated (Ren et al 2012). Only the latter showed CLL specificity (see Fig.…”
Section: Transcriptional Chimeras In Cllmentioning
confidence: 96%
See 1 more Smart Citation
“…We also analyzed other cancer studies where chimeric genes have been reported. In our full set of chimeric junctions (see Methods section ''Chimeric junctions'') we found five chimeric read-through events previously identified, LAMTOR1-ANAPC15 and PTPRG-C3orf14 in melanoma (Berger et al 2010), TATDN1-MTSS1 and MAP2K7-SNAPC2 in CLL (Velusamy et al 2013), and TTTY15-USP9Y found in prostate cancer and experimentally validated (Ren et al 2012). Only the latter showed CLL specificity (see Fig.…”
Section: Transcriptional Chimeras In Cllmentioning
confidence: 96%
“…S10a,b). Recently, Velusamy and colleagues have reported a recurrent and reciprocal chimera between YPEL5 and PPP1CB genes (Velusamy et al 2013). This recurrence was reported to be as high as 95% of the CLL samples but negative in normal samples using qPCR.…”
Section: Transcriptional Chimeras In Cllmentioning
confidence: 99%
“…All assays were performed in triplicate and repeated two times and results were plotted as average fold change relative to GAPDH. 39 Primers used for detecting b-TrCP, p16 Ink4a or GAPDH are as follows: b-TrCP F (5 0 -TCATAACTGCTCTGCCAGCTCGGG-3 0 ), b-TrCP R (5 0 -ATCCTCTTC GTTCTGCCAGGCC-3 0 ), CDKN2A F (5 0 -GGGCTCTCACAACTAGGAAAG-3 0 ), CDKN2A R (5 0 -GGTGTTTGGTGTCATAGGG-3 0 ), CDKN1A F (5 0 -AGGTGGACC TGGAGACTCTCAG-3 0 ), CDKN1A R (5 0 -TCCTCTTGGAGAAGATCAGCCG-3 0 ), GAPDH F (5 0 -TGCACCACCAACTGCTTAGC-3 0 ) and GAPDH R (5 0 -GGCATGG ACTGTGGTCATGAG-3 0 ).…”
Section: Western Blot Analyses and Determination Of Protein Half-lifementioning
confidence: 97%
“…Besides JAZF1-JJAZ1 , reports for other chimeric RNAs generated by non-chromosomal rearrangement mechanisms are also emerging. Recently, reciprocal RNA chimera involving YPEL5 and PPP1CB was identifi ed by transcriptome sequencing, and no corresponding rearrangement at the DNA level was found ( 4 ). In addition, we reported cis -splicing of adjacent genes as another mechanism to generate SLC45A3-ELK4 chimera involving neighboring genes transcribing in the same direction ( 5 ).…”
Section: Introductionmentioning
confidence: 93%